Pay Policy Reform : Building a Foundation for Public Sector Performance Through Improved Public Sector Pay Policy by Using a "Single Pay Spine" - Green, Malcolm (World Bank, Washington, DC, 2012)
Appropriate public sector remuneration policies are key for performance. They can motivate staff to a limited extent by rewarding performance but more generally by eliminating inequities and avoiding frequent and sudden changes in pay. They can also assist in retaining competent staff one of the most critical drivers of public sector performance. Developing pay policy in the public sector is complex, administratively and politically. This note analyzes one approach to creating a fiscally sustainable, equitable and performance enhancing pay policy, the single pay spine. It focuses on the single pay spine as a means to help countries achieve four pay policy objectives: 1) ensuring that public service pay is affordable; 2) achieving competitiveness with pay outside the public service; 3) promoting greater transparency in public pay; and 4) ensuring that there is equal pay for equal work (i.e. eliminating inequity).